2021
DOI: 10.3390/atmos12070813
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric Imaging vs. Conventional Imaging: Evaluation of Image Contrast in Fog

Abstract: We compare conventional intensity imaging against different modes of polarimetric imaging by evaluating the image contrast of images taken in a controlled foggy environment. A small-scale fog chamber has been designed and constructed to create the necessary controlled foggy environment. A division-of-focal-plane camera of linear polarization and a linearly polarized light source has been used for performing the experiments with polarized light. In order to evaluate the image contrast of the different imaging m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Simultaneously, an active LiDAR system measured the same scene using a circularly polarized beam and provided the same conclusions in the infrared wavelength of 1064nm [164]. These results agree with the work of [189] where distinct materials embedded in fog are measured under active illumination and CROSS circular channel outperforms in dielectric materials.…”
Section: Reflection Scheme Detectionsupporting
confidence: 83%
See 2 more Smart Citations
“…Simultaneously, an active LiDAR system measured the same scene using a circularly polarized beam and provided the same conclusions in the infrared wavelength of 1064nm [164]. These results agree with the work of [189] where distinct materials embedded in fog are measured under active illumination and CROSS circular channel outperforms in dielectric materials.…”
Section: Reflection Scheme Detectionsupporting
confidence: 83%
“…Many studies have been performed to see in turbid media using polarization property as introduced in Section 2.5.1, but the majority of them perform their studies applying the physical filtering of measuring with specific polarization states in the camera to detect embedded objects, as previously done with the modified DoFP. Other research have shown the usefulness of linear combinations between channels of the PSA such as difference between CO and CROSS to improve detection [166,189], in the same manner as in Figure 7.9. Based on this last evidence, the next step in the analysis of detection through turbid media is to employ the DoAPC to acquire the full Stokes images and see the complete polarization response of the scattering media.…”
Section: Active Imaging Full-stokes Doapcmentioning
confidence: 79%
See 1 more Smart Citation
“…For imaging, whenever we know that the elements of the scene will behave like ordinary targets (metals, ground, living beings, etc. )-which are either depolarizing for mostly dielectric surfaces, or reflecting co-polarized state for LP incident light and cross-polarized state for CP incident light, in the case of metallic surfaces [12,17]-the CROSS circular channel is going to show the best performance, with the maximum image contrast. So, in the CROSS circular case, while targets will mainly return non-polarized or circularly cross-polarized light, and thus, their signal will be detected, the media response will be filtered because the signal will mainly be in the circularly co-polarized component.…”
Section: Resultsmentioning
confidence: 99%
“…In general, polarized light reflected from ordinary targets is mostly depolarized, with a smaller polarized component in the co-polarized state for linearly incident light and in the cross-polarized state for circularly incident light. Nevertheless, this dependence may vary on the specific material of the object [12,17].…”
Section: Introductionmentioning
confidence: 99%